1998
DOI: 10.1037/0022-0663.90.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Help giving in achievement contexts: A developmental and cultural analysis of the effects of children's attributions and affects on their willingness to help.

Abstract: This developmental and cultural study investigated the impact children's attributions and affects have on their willingness to help in achievement contexts. B. Weiner's (1980a) attribution-emotion-action model was extended in order to consider a peer's responsibility for the cause of his or her need for help (onset responsibility) and the solution to the problem (offset responsibility). The 145 Anglo and Chinese American elementary and middle school student participants read 4 scenarios that manipulated the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Karasawa (1991), for example, reported strong and pervasive negative evaluations among college students when evaluating a peer described as falling behind on a class group project as a result of low effort. Bennett and Flores (1998) replicated these findings among elementary and middle school age children and reported that participants viewed a low-effort peer with greater anger, blame, and perceptions of responsibility. Participants also responded to the peer with less pity and less willingness to provide assistance.…”
Section: The Impact Of Perceived Effort On Evaluationssupporting
confidence: 72%
See 2 more Smart Citations
“…Karasawa (1991), for example, reported strong and pervasive negative evaluations among college students when evaluating a peer described as falling behind on a class group project as a result of low effort. Bennett and Flores (1998) replicated these findings among elementary and middle school age children and reported that participants viewed a low-effort peer with greater anger, blame, and perceptions of responsibility. Participants also responded to the peer with less pity and less willingness to provide assistance.…”
Section: The Impact Of Perceived Effort On Evaluationssupporting
confidence: 72%
“…In the present study, we examined children's sensitivity and responsiveness to displayed effort cues that children are likely to encounter in day-to-day classroom interactions (e.g., work habits) but that do not involve dependency on the low-effort peer's academic success. Bennett and Flores (1998) noted that any factor that increases the salience or effect of effort cues may have significant implications for social interactions such as help-giving behavior. One of the most common ways that a child's effort and achievement outcomes might be highlighted among peers is through group discussion.…”
Section: Perceived Effort and Peer Evaluationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In prior investigations (e.g., Barnett et al., ; Sonnentag et al., ), children's attribution of fault has often been assessed using a single, general statement (e.g., ‘It is this boy's fault that he is _______’). Although general attributions of fault are associated with children's anticipated responses to peers with various undesirable characteristics (see also Sigelman & Begley, ), several studies suggest that children's fault attributions may involve a more complex understanding that peers can be responsible for the origin (i.e., onset) and/or the continuation (i.e., perpetuation) of a personal problem (e.g., Bennett & Flores, ; Brickman et al., ; Karasawa, ). Furthermore, these presumably independent attributions of fault may differentially impact how children respond to a peer with an undesirable characteristic (Brickman et al., ).…”
Section: Studymentioning
confidence: 99%
“…Research guided by Weiner's (1995) model has reliably explained disparate social phenomena, such as aggression (Eaton & Struthers, 2006); political ideology (Zucker & Weiner, 1993); reactions to stigma (Weiner, 1993); workplace conflict resolution and personnel selection (Struthers, Miller, Boudens, & Briggs, 2001; Struthers, Weiner, & Allred, 1998); as well as helping (Bennett & Flores, 1998; Greitemeyer et al., 2003; Reisenzein, 1986). It is only recently, however, that researchers have begun examining whether the model applies as well to group targets as it does to individual targets.…”
Section: Why People Help: An Attributional Approachmentioning
confidence: 99%